2010
DOI: 10.1177/1534765610388305
|View full text |Cite
|
Sign up to set email alerts
|

Cultural considerations in trauma psychology education, research, and training.

Abstract: The fields of trauma psychology and cultural psychology have rarely crossed paths within the context of mainstream psychology and psychiatry. Although clinical trauma psychology has acknowledged relevance of the ethical principle of respect for differences in trauma treatment, this has not so far motivated a systematic effort to improve our understanding of how culture is intertwined with our cognitive and emotional responses to trauma. As the field of disaster mental health has come to greater prominence in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Regarding cultural appropriateness, one suggestion for future research into traumatic stress, depression and anxiety would be to adjust instrument scoring to represent cultural expression of trauma symptoms; and to develop appendices containing culturally-appropriate questions about trauma and culturally-appropriate lists of trauma events (Mattar, 2010). For example, among Tibetans, the most traumatic event is considered to be the destruction or desecration of religious objects and icons, an item that does not appear in the Harvard Trauma Questionnaire (but presumably would be reported in the open question in Part 1, Item 46, a question that asks about “other traumatic events” not previously discussed in the interview).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cultural appropriateness, one suggestion for future research into traumatic stress, depression and anxiety would be to adjust instrument scoring to represent cultural expression of trauma symptoms; and to develop appendices containing culturally-appropriate questions about trauma and culturally-appropriate lists of trauma events (Mattar, 2010). For example, among Tibetans, the most traumatic event is considered to be the destruction or desecration of religious objects and icons, an item that does not appear in the Harvard Trauma Questionnaire (but presumably would be reported in the open question in Part 1, Item 46, a question that asks about “other traumatic events” not previously discussed in the interview).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a final written assignment called for the integration of knowledge from the literature with personal experiences, feelings, and thoughts during the journey. Mattar (2010) indicated that while in the field of traumatology there has been a slow but steady acknowledgment of the importance of cultural sensitivity in understanding and addressing trauma, recommendations on how to do this and how to prepare practitioners to adopt a culturally sensitive approach to those who are traumatized are limited.…”
Section: Teaching About Cultural Diversitymentioning
confidence: 99%
“…Several site visits offered students an opportunity to learn about the combined effects of traumatic exposure and diversity as a means for learning to incorporate a cultural lens in trauma work. This was done using a broad notion of culture that included, in addition to ethnicity, socio-economic status, immigrant/refugee status, education level, and religiosity, as well as by providing opportunities for meetings with representatives of different underprivileged groups (Mattar, 2010). For example, in a visit to a coffee shop run by youth in distress in Sderot, a town heavily populated by immigrants with a high unemployment rate, which for over a decade has been consistently bombed from the nearby Gaza strip, students learned from clients about their experience of exposure to multiple stressors (immigration, poverty, living under constant security threat) and from workers about the experience of ‘shared trauma’ and strategies that they used.…”
Section: Teaching About the Intersection Of Culture And Traumamentioning
confidence: 99%
“…Whether new or seasoned to the practice of trauma treatment, it is essential that therapists receive ongoing education regarding new research and best practice findings to achieve, increase, or maintain their levels of competence (Canadian Centre on Substance Abuse, 2012;CPA, 2000;Mattar, 2010). Based on the work of Dr. Stephanie Covington, the Canadian Centre on Substance Abuse (2012) cited four key principles that are believed to be essential learning for practitioners in providing trauma-informed care such as trauma awareness including its wide-ranging impact on human beings, the ability to establish an environment of physical and emotional safety and trust, the importance of providing clients with "opportunity for choice, collaboration, and connection" (p. 3), and the use of strengths-based and skilldeveloping approaches in trauma treatment.…”
Section: Supervision and Other Professional Activitiesmentioning
confidence: 99%